KOMBINASI INJEKSI sGNRH-a + ad , PADA KETINGGIAN AIR YANG BERBEDA UNTUK PEMIJAHAN SNAKEHEAD , Channa Striata DI WADAH BUDIDAYA - Untung Bijaksana Bijaksana; Septiodrian R. Balantek (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2019)
This study aims to look at the effectiveness of injection of sGnRH-a + ad andheight of water on fish spawning snakehead, Channa striata in the concreat tank.The research was conducted at the Wet Laboratory Aguaculture Departement Faculty of Fisheries University of Lambung Mangkurat. There are two main factors as treatment namely: Factor A = dose of sGnRH-a + ad with three levels (A1 = 0.2 ml /kg; A2 = 0.4 ml / kg; A3 = 0.6 ml / kg) and factor B = height of water with three levels(B1 = 15 cm; B2 = 20 cm; B3 = 25 cm) made repeated 4 times to obtain 36 units of the experiment. Observations made on the parameters: body weight, gonad weight,liver weight, estradiol-17β, egg diameter, IGS, IHS, fecundity, fertilization andhatching degrees. The strongest relationship obtained from the treatment of observational parameter is IGS and IHS. Of treatment given the latent time of theobtained range between 12 hours to 25 hours, fecundity between 5047 to 5072grains, the degree of fertilization between 60 to 60.3 percent and 76.6 degrees fertilization between 83.9 per cent up. Developments after hatching body length of3.5 mm and 45.5 mm on day 20.